A rare tumor at an unusual site-angiomyolipoma vulva - Dubey, Vikas; Gupta, Neelam; Puri, Monica; Blaggan, Ankush (International Journal of Research in Medical Sciences, 2021)
An angiomyolipoma is one of the very rare benign tumors. All three elements, that is, blood vessels, adipose tissue and smooth muscles, should be present to qualify it to be labelled as an ‘angiomyolipoma’. Although it has been reported at other sites also like mediastinum, heart, spermatic cord, fallopian tube, oral cavity, penis, salivary glands, and skin.